External influences on English from its beginnings to the Renaissance - Miller, D. Gary. (Oxford : Oxford University Press, 2012)
In this fascinating history of the influences on English during the first thousand years of its formation the author shows when and why the Anglo-Saxons began to borrow words from Latin and Greek and the effects of contact with the Vikings, Celts, and French.
Description based on online resource; title from PDF title page (viewed on July 9, 2012).
Includes bibliographical references and index.
Keywords: English language -- Foreign elements; English language -- Etymology